St. Thomas More: a preliminary bibliography of his works and of Moreana to the year 1750. Comp. by R.W. Gibson. With a bibliography of Utopiana comp. by R.W. Gibson and J.M. Patrick (Yale University Press, 1961)
With ills and index.